Franchisor-franchisee relationship and performance: influence of personality traits, entrepreneurial drive, and time of relationship - Varotto, Luís Fernando (2015)
Literature in franchise has virtually ignored the role of psychological aspects on firm interorganizational results, despite its influence on firm level results and relationship quality. Therefore, the present study aims to examine the influence of franchisees’ personality and entrepreneurial drive on franchisor-franchisee relationship quality and financial performance over time. The study also investigated the role of the time of relationship on the relationship quality and financial performance. This study used a self-report survey conducted by mail to collect data from a sample of 342 franchisees selected from 3 franchise networks. Personality was represented by the Big-Five personality traits (IPIP-B5 scales): extraversion, agreeableness, conscientiousness, emotional stability, and imagination. Entrepreneur drive was represented by the Carland Entrepreneurship Index (CEI). Relationship quality was conceptualized through a 23-item second-order construct (incorporating trust, commitment, and relationship satisfaction), while financial performance was represented by using a scale measuring sales growth and profitability. Time of relationship was measured by the months of relationship between franchisee and franchisor. A Partial Least Squares (PLS) structural equation model, mean analysis, and regression analysis were conducted to test the hypothesized relationships. Three of the five personality dimensions produced the predicted effect on the outcome variables of relationship quality – agreeableness (positively), emotional stability (positively), and imagination (positively). Financial performance was affected as predicted by conscientiousness (positively), emotional stability (positively), and imagination (positively). As expected, relationship quality presented a positive and significant effect on financial performance. Entrepreneurial drive showed the predicted positive effect only on performance. Time of relationship presented the positive predicted effect on the franchisor-franchisee relationship as regards relationship quality and financial performance; however, the hypothesized shape of the relationship phases could only partially be confirmed, since only between two phases (routine and stabilization) mean analysis showed significant differences. Results indicate that personality does in fact influence relationship quality and performance, but the manner in which this occurs differs from the Brazilian context where this research was conducted to the findings of research conducted in Australia, suggesting that factors such as culture and market stability may have influence on the relationship between personality traits and both relationship quality and financial performance. Entrepreneurial drive appears to positively influence franchisee performance, but its influence proved not to produce a significant impact on relationship quality. The present study’s results also indicate the importance of the time of relationship needed to foster relationship quality and performance. Moreover, long-term relationships are related to better franchisee relationship quality and financial performance assessments. Limitations of this work and suggestions for future studies are also discussed.